2022
DOI: 10.1038/s41598-022-07994-8
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude setting and dopamine response of finger tapping and gait are related in Parkinson’s disease

Abstract: Movement amplitude setting is affected early in Parkinson’s disease (PD), clinically manifesting as bradykinesia. Our objective was to determine if amplitude setting of upper limb bimanual movements and bipedal gait are similarly modulated in PD. 27 PD and 24 control participants were enrolled. Participants performed a bimanual anti-phase finger tapping task wearing gloves with joint angular sensors, and an instrumented gait assessment. Participants performed normal and fast paced assessments to vary motor loa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Tapping behaviors have been demonstrated to be affected early in disease 1 , relate to disease severity 2 , 21 , and have been successfully deployed on mobile phone based platforms for real world data collection 18 20 . We have also previously shown in a simple tapping task, as in the more advanced game described in this work, that finger tapping amplitude relates to gait stride-length 17 . Our game adds to simple tapping tasks by incorporating a visual game that simulates gait by walking a frog through a maze environment using bimanual movements akin to bipedal gait.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Tapping behaviors have been demonstrated to be affected early in disease 1 , relate to disease severity 2 , 21 , and have been successfully deployed on mobile phone based platforms for real world data collection 18 20 . We have also previously shown in a simple tapping task, as in the more advanced game described in this work, that finger tapping amplitude relates to gait stride-length 17 . Our game adds to simple tapping tasks by incorporating a visual game that simulates gait by walking a frog through a maze environment using bimanual movements akin to bipedal gait.…”
Section: Discussionmentioning
confidence: 54%
“…Repetitive tapping tasks have been used to study bradykinesia in PD 1 , 13 , have been used to evaluate upper limb freezing 14 , 15 , and have demonstrated the sequence effect 16 which manifests as a decrement in amplitude that precedes freezing episodes. We previously showed that tap amplitude on a bimanual finger tapping task was correlated to gait stride-length in individuals with PD in the levodopa OFF state 17 . Tap amplitude on this task also improved with levodopa proportionally to the improvement seen in stride-length with levodopa.…”
Section: Introductionmentioning
confidence: 99%
“…Tapping behaviors have been demonstrated to be affected early in disease 1 , relate to disease severity 2,21 , and have been successfully deployed on mobile phone based platforms for real world data collection [18][19][20] . We have also previously shown in a simple tapping task, as in the more advanced game described in this work, that nger tapping amplitude relates to gait stride-length 17 . Our game adds to simple tapping tasks by incorporating a visual game that simulates gait by walking a frog through a maze environment using bimanual movements akin to bipedal gait.…”
Section: Subgroup Analysis Of Gait Freezers Vs Non-freezers On the Fr...mentioning
confidence: 55%
“…12 Repetitive tapping tasks have been used to study bradykinesia in PD 1,13 , have been used to evaluate upper limb freezing 14,15 , and have demonstrated the sequence effect 16 which manifests as a decrement in amplitude that precedes freezing episodes. We previously showed that tap amplitude on a bimanual nger tapping task was correlated to gait stride-length in individuals with PD in the levodopa OFF state 17 . Tap amplitude on this task also improved with levodopa proportionally to the improvement seen in stridelength with levodopa.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous monitoring can lead to an early diagnosis of further neurological deterioration, assessment of disease progression and help the clinicians in evaluating treatment effectiveness [13]. Tremor frequency and amplitude are two clinically significant parameters that indicate tremor severity [14]- [17]. Both parameters are vital in the differential diagnosis of tremor-related diseases, for example, to rule out PD versus ET, where symptoms might be confusing [18].…”
Section: Introductionmentioning
confidence: 99%